Corporate Governance Practices in India: A Comparative Analysis of Senior and Middle Managers - Grover, Dimple (International Journal of Social Sciences and Management, 2022)
Employees create wealth and bring sustainability to an organization. The organizations are building on their strength by adopting to the best governance mechanisms making employees as the enablers. The current paper investigates the perceptual differences of Senior & Junior Managers in the context of CG practices within an organization. A sample of 255 employees from various public and private sector were assessed. The findings point towards difference between Senior and Junior Managers. Management Processes emerged as a significant variable. Int. J. Soc. Sc. Manage. Vol. 9, Issue-2: 63-66.